2005
DOI: 10.1161/01.atv.0000166601.49954.21
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Matrix-Degrading Protease Expression and Activity Between Thrombus-Free and Thrombus-Covered Wall of Abdominal Aortic Aneurysm

Abstract: The present work demonstrates that protease expression and activity differs within the aneurysm wall. The source and activity of the proteases responsible for the degradation of the thrombus-covered wall need to be further determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 36 publications
1
66
0
Order By: Relevance
“…The role of the thrombus in aneurysm expansion and rupture is uncertain. 30,32,33 Some macrophages are present deep within the thrombus, but, alternatively, this signal pattern may reflect USPIO within the canaliculi that traverse the thrombus, conducting fluid, small molecules and, to a certain extent, cells from the lumen toward the aortic wall. 30 This pattern of USPIO uptake and inflammation within the thrombus is of uncertain significance but interestingly did not appear to be associated with accelerated aneurysm growth.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the thrombus in aneurysm expansion and rupture is uncertain. 30,32,33 Some macrophages are present deep within the thrombus, but, alternatively, this signal pattern may reflect USPIO within the canaliculi that traverse the thrombus, conducting fluid, small molecules and, to a certain extent, cells from the lumen toward the aortic wall. 30 This pattern of USPIO uptake and inflammation within the thrombus is of uncertain significance but interestingly did not appear to be associated with accelerated aneurysm growth.…”
Section: Discussionmentioning
confidence: 99%
“…14) Kazi, et al also demonstrated that upregulation of MMPs was found in the aneurysm wall without thrombus. 15) Our data indicate that the relationship between ILT of AAA and MMPs may be associated with AAA sac shrinkage after EVAR. Cornelissen, et al reported that recent use of magnetic resonance imaging (MRI) in some cases, as a method of evaluating the size of aneurysm sac after EVAR, revealed that half of the non-shrinking aneurysm sac contents consisted of unorganized thrombus several years after EVAR.…”
Section: Discussionmentioning
confidence: 59%
“…Production of MMPs by macrophages under these conditions are believed to be implicated in weakening of arterial walls (Vorp, et al, 2001) (Kazi, et al, 2005) (Murdoch, et al, 2005) (Oya, et al, 2011). In the present study, we focused on the effect of oxygen concentrations on MMP production of macrophages subjected to cyclic stretching.…”
Section: Discussionmentioning
confidence: 99%
“…Studies for AAA tissues have found extensive inflammatory infiltrates such as macrophages and T lymphocytes (Bobryshev, et al, 1998) (Pearce and Koch, 1996), and increased expression of MMPs (Thompson, et al, 1995), which is a family of enzymes that proteolytically degrade various components of the extracellular matrix. Since MMP-9, the most abundant gelatinolytic MMP and secreted in high levels in AAA tissue (Thompson, et al, 1995), colocalized with infiltrated macrophages (Kazi, et al, 2005), functions of macrophages under AAA walls conditions have been examined in association of formation and enlargement of aneurysms.…”
Section: Introductionmentioning
confidence: 99%